The effect of trainee characteristics, learning styles and organisational factors on effective end-user training in four New Zealand organisations : a multiple case study : a thesis presented in partial fulfillment of the requirements for the degree of Master of Information Science in Information Systems at Massey University - Shand, Jane Isabel (Massey University, 2002)
This study represents the results of a one-year thesis project into the effectiveness of End User Training (EUT) of software applications in four large organisations in New Zealand. The ubiquity and criticality to successful business of desktop computers in business organisations in the twenty-first century is unchallenged. Information Systems (IS) research over the past thirty years has consistently identified that the success of IS is heavily dependent on the skills and knowledge of the end users of those systems. Further, a large IS research effort has identified that a critical success factor of skilled and knowledgeable users is effective EUT. Governments and organisations world-wide recognise and expend considerable resources on improving the increase of knowledge and skills of workers, with particular focus and emphasis, in more recent years, on EUT. This project has identified and emphasised the large number of factors that impact on the effectiveness of EUT. Focus has been on identifying factors that are particularly pertinent to practitioners in the New Zealand environment in order to provide a rigorous academic framework for future practical EUT. Multiple case study methodology has enabled the project to provide a rich picture of the organisational environment that surround EUT in large New Zealand organisations. Analysis of data in the study has identified four trainee characteristics that impacted on the results of EUT. Additionally, the study found that organisational factors to support EUT and training method when optimally combined with trainee characteristics and learning styles, could provide essential information for effective EUT design and delivery in New Zealand organisations. As this study was exploratory in nature, there is opportunity for IS researchers to explore and explain in greater detail a range of factors that both produce and predict greater effectiveness in EUT.
Keywords: End-user computing; End-user training